Incontinência urinária específica da gestação e a sua relação com a funcionalidade dos músculos do assoalho pélvico - Gueza, Bianca de Almeida [UNESP]; Primo, Ingrid Emilena Brito [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Introduction: Urinary incontinence (UI) is defined as the involuntary loss of urine. Pregnancy represents a cycle of great changes for the woman’s body and for the pelvic floor muscles, due to the weight of the fetus and the placenta, which can trigger specific pregnancy urinary incontinence (UI-EG). Objective: The objective of the present study was to analyze the IU-EG and its relationship with the functionality of the pelvic floor muscles (PFM). Method: The study was carried out with pregnant women from 18 years old, at any gestational moment from 24 weeks, normoglycemic, urinary continents prior to the current pregnancy, without degenerative muscle diseases and who had never previously performed MAP training. The ICIQ-SF questionnaire was applied, which covers the frequency of urinary loss, volume and impact and the ISI questionnaire that says about the frequency and amount of urine loss. Results: Participated in the study 257 pregnant women participated in the study, being distributed according to the state of continence, 113 continents and 144 with IU-EG. The groups were matched for gestational age, maternal weight gain, and ethnicity. The EG-IU group was significantly younger than the continent group (p=0.010), had a higher pre-pregnancy BMI (p=0.001) and a higher BMI during pregnancy (p=0.002). The prevalence of parity with a previous cesarean section was also higher in the IU-EG group (p=0.045). The IU-EG group had moderate incontinence severity. Regarding the PFM function, there were differences between the groups in strength and resistance. The IU-EG presented lower strength evaluated during the AFA, in this group the frequencies of pregnant women who presented lower performance (MOS: 0-2) were higher than the continent groups. In addition, the IU-EG had a shorter time to sustain the contraction of the PFM, compared to the continent group. There was no difference between the groups regarding the number of repetitions of PFM contractions (p=0.079). Conclusion: It was concluded with the results of the analysis of this sample, it can be concluded that the IU-EG group has less strength and shorter PFM sustaining time.

Introdução: A incontinência urinária é definida como a perda involuntária de urina. A gestação representa ciclo de grandes mudanças para o corpo da mulher e para os músculos do assoalho pélvico, devido ao peso do feto e da placenta, podendo desencadear a incontinência urinaria especifica da gestação (IU-EG). Objetivo: O objetivo do presente estudo foi analisar a IU-EG e a sua relação com a funcionalidade dos músculos do assoalho pélvico (MAP). Método: O estudo foi realizado com gestantes a partir de 18 anos, em qualquer momento gestacional a partir de 24 semanas, normoglicêmicas, continentes urinarias previas a atual gestação, sem doenças musculares degenerativas e que nunca tenham realizado previamente treinamento dos MAP. Foi aplicado o questionário ICIQ-SF que abrange a frequência da perda urinaria, o volume e o impacto e o questionário ISI que diz a respeito da frequência e quantidade da perda de urina. Resultados: Participaram do estudo 257 gestantes sendo distribuídas de acordo com o estado de continência, 113 continentes e 144 com IU-EG. Os grupos foram pareados quanto à idade gestacional, ganho de peso materno e etnia. O grupo IU-EG foi significativamente mais jovem do que o grupo continente (p=0,010), apresentou maior IMC pré-gestacional (p=0,001) e IMC durante a gestação (p=0,002). A prevalência de paridade com uma cesariana prévia também foi maior no grupo IU-EG (p=0,045). O grupo IU-EG apresentou gravidade de incontinência moderada. Em relação à função dos MAP houve diferenças entre os grupos na força e resistência. A IU-EG apresentou menor força avaliada durante a AFA, neste grupo as frequências de gestantes que apresentaram menor desempenho foram maiores que os grupos das continentes. Além disso, os IU-EG apresentaram menor tempo de sustentação da contração dos MAP, em comparação ao grupo continente. Não houve diferença entre os grupos em relação ao número de repetições das contrações dos MAP (p=0,079). Conclusão: Com os resultados da análise desta amostra pode-se concluir que o grupo IU-EG tem menor força e menor tempo de sustentação dos MAP.
Pregnancy-specific urinary incontinence and its relationship to the functionality of the pelvic floor muscles
Keywords: Pelvic floor; Gestation; Parity and urinary incontinence; Assoalho pélvico; Gestação e incontinência urinária